Anti-aging Effect of Panax notoginseng Saponins via Protecting Endogenous Antioxidant in Fruit Flies - Zou, Yingxin; Ju, Dawei; Liu, Fei; Liu, Weihong; Chu, Zhiyong (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Panax notoginseng saponins (PNS), the main active ingredients extracted from Panax notoginseng, are chemical mixtures, with the five main active components of ginsenosides Rg1, Rb1, Re, Rd and notoginsenoside R1. Objectives: The present study investigated the effect of PNS on anti-aging in fruit flies, which represented as a natural physical organism aging model. Materials and Methods: After lifelong supplement of PNS in the culture medium at the concentration of 50, 100 and 200 mg/L, the reproduction and the lifespan were observed in fruit flies. The activity of total antioxidative capabilities (T-AOC), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-px) were detected to evaluate oxidative stress levels. Results: Lifelong supplement of 50 mg/L PNS significantly prolonged the lifespan of fruit flies (Log rank χ2 =6.752, P=0.009); supplement of 100 mg/L PNS tendency increased the lifespan of fruit flies with no significance; while supplement of 200 mg/L PNS potentially accelerated the death of fruit flies with no significance. Supplement of 50 mg/L PNS protected the reproductive capacity (p<0.05 for 15 and 30 days) in fruit flies. The activity of T-AOC, CAT, total SOD (T-SOD) and GSH-px significantly or tendency increased by 50, 100 and 200 mg/L PNS. Conclusion: Supplement of 50 mg/L PNS prolonged the lifespan and protected the reproductive capacity of fruit flies. The mechanism might be, at least in part, through the anti-oxidative stress pathway by protecting the activity of T-AOC, CAT, T-SOD and GSH-px. Supplement of 200 mg/L PNS might be toxic for fruit flies.
Keywords: Panax notoginseng saponins; Aging; Lifespan; Reproduction; Antioxidant enzyme